IMPLEMENTASI GURU SEJARAH DALAM MENERAPKAN KURIKULUM 2013 DI KELAS X DI SMA N 1 REMBANG TAHUN AJARAN 2014/2015 - Sutarman, Eko (Indonesian Journal of History Education, 2015)
This study used qualitative research methods so as to produce a data description. These results indicate that the perception of each teacher to the curriculum in 2013 in Apex senior high school has been positive. In theory the teachers already have a good knowledge and understanding of the curriculum of 2013. Implementation of history teachers in implementing the curriculum in 2013 in the class is good enough. But in practice can not be perfect teachers apply the scientific approach, so that almost every meeting using discussions and lectures, though never for learning outside the classroom to the Sangiran museum. Constraints that teachers face is the lack of specialization history handbook of government, school infrastructure that still needs improvement, socialization and training on curriculum continued. Â